Effect of vasopressin V2-receptor antagonist tolvaptan on syndrome of inappropriate antidiuresis (SIAD) after transsphenoidal pituitary surgery: recovery of measured osmolality. Issue 10 (October 2022) - Tosaka, Masahiko; Yamaguchi, Rei; Itabashi, Yutaro; Mukada, Naoto; Tsuneoka, Haruka; Takahashi, Kentaro; Nakamura, Shunsuke; Nakazawa, Takahiko; Yoshimoto, Yuhei
Abstract: Background: Delayed hyponatremia after pituitary surgery can be treated with the V2-receptor antagonist, oral tolvaptan. We investigated the pharmacological effect of oral tolvaptan against SIAD in patients with hyponatremia after pituitary surgery. Methods: Thirty-nine patients with pituitary adenoma treated by endoscopic transsphenoidal surgery developed SIAD according to the major guidelines, and 7 patients (17.9%) were treated with tolvaptan. Tolvaptan was administrated orally half a tablet (3.75 mg) once in the first two cases, and half a tablet twice in the other five cases. Serum osmolality, urinary osmolality, urinary sodium concentration, urinary volume, and serum sodium and potassium concentration were evaluated before administration, and after the last oral administration of tolvaptan. Serum osmolality and urine osmolality were physically measured. Results: Serum sodium concentration was significantly increased from 132.1 ± 4.0 to 143.0 ± 2.9 mmol/L (mean ± standard deviation, n = 7, P < 0.001). Serum osmolality was significantly increased from 266.3 ± 7.7 to 289.6 ± 6.7 mOsm/kg (n = 7, P < 0.001). Urine osmolality was significantly reduced from 607.1 ± 240.4 to 262.7 ± 115.6 mOsm/kg (n = 7, P = 0.01). Urinary sodium concentration was significantly decreased from 121.3 ± 48.4 to 36.9 ± 35.0 mOsm/kg (n = 7, P = 0.001). Urine output (24-hour including the first administration) was significantly increased from 1384.2 ± 550.7 to 3291.3 ± 1710.9 mL/day (n = 6, P = 0.026). Conclusions: Oral tolvaptan administration corrects SIAD after pituitary surgery. Hyponatremia after pituitary surgery was confirmed to be due to SIAD. Abstract : Tolvaptan; Vasopressin V2-receptor antagonist; Hyponatremia; Pituitary; Surgery.